2018
DOI: 10.1101/494716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cheaters shape the evolution of phenotypic heterogeneity in Bacillus subtilis biofilms

Abstract: Biofilms are closely packed cells held and shielded by extracellular matrix composed of structural proteins and exopolysaccharides (EPS). As matrix components are costly to produce and shared within the population, EPS-deficient cells can act as cheaters by gaining benefits from the cooperative nature of EPS producers. Remarkably, genetically programmed EPS producers can also exhibit phenotypic heterogeneity at single cell level. For instance, mature biofilms of Bacillus subtilis contain cells in an 'ON' state… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The emergence of variants with lower or diminished matrix production in the B. subtilis biofilm raises the question of how such non-producers affect matrix production in the cooperative members of the population. Mutants deficient in production of EPS are not able to form robust pellicles alone, but can take advantage of the EPS-producing wild type, incorporate into the biofilm, and simultaneously save metabolic costs and exploiting a public good [34,39,61,62]. Experimental evolution has been performed on pellicles established by cooperative wild-type cells harboring a reporter for EPS production and non-producers that lack EPS production.…”
Section: The Impact Of Intra-species Interaction On the Evolution Of Phenotypic Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of variants with lower or diminished matrix production in the B. subtilis biofilm raises the question of how such non-producers affect matrix production in the cooperative members of the population. Mutants deficient in production of EPS are not able to form robust pellicles alone, but can take advantage of the EPS-producing wild type, incorporate into the biofilm, and simultaneously save metabolic costs and exploiting a public good [34,39,61,62]. Experimental evolution has been performed on pellicles established by cooperative wild-type cells harboring a reporter for EPS production and non-producers that lack EPS production.…”
Section: The Impact Of Intra-species Interaction On the Evolution Of Phenotypic Heterogeneitymentioning
confidence: 99%
“…Experimental evolution has been performed on pellicles established by cooperative wild-type cells harboring a reporter for EPS production and non-producers that lack EPS production. These experiments revealed that in response to eps mutant incorporation into the B. subtilis pellicles, the wild type undergoes evolutionary adaptation by shifting the phenotypic heterogeneity of eps gene expression and becomes a matrix overproducer (hyper-ON), so that most of the cells express the eps genes [61]. At the same time, the fraction of eps mutants increases in the population that may result in the collapse of these populations where no pellicle is produced upon re-inoculation of the bacterial culture.…”
Section: The Impact Of Intra-species Interaction On the Evolution Of Phenotypic Heterogeneitymentioning
confidence: 99%